THE EFFECT OF REWARDS AND PUNISHMENTS ON EMPLOYEE WORK MOTIVATION AT PT. CATUR PUTRA JAYA DEPOK BRANCH - Karmelia, Anita; Firdaus, Muhamad Azis; Subakti, Jani (Universitas Ibn Khaldun Bogor, 2025)
The purpose of this study is to examine how rewards and penalties affect PT. Catur Putra Jaya Depok Branch employees' motivation for their work. With a population of 85 employees, this study employs a quantitative methodology and gathers data using questionnaires. Data analysis was done using validity, reliability, multiple linear regression, t-test, f-test, and determination coefficient (R2). The results of the validity test showed that all questionnaire items were valid with a value of r calculated > r table (0.213). Every variable in the reliability test has a Cronbach's Alpha value greater than 0.6, so it is declared reliable. Partially, the award has a correlation coefficient of 0.430 with a significance of 0.000 < 0.05, and the punishment has a significance level of 0.000 > 0.05 an a correlation value of 0.477, showing that both have a significant effect on work motivation. Simultaneously, the coefficient of determination (R2) was 0.228, which indicates that 22.8% of the difference in employee work motivation was influenced by rewards and punishments, while the rest of 77.2% was impacted by other factors that were not studied. Thus, companies are advised to improve the reward system and strengthen the application of penalties so that employee work motivation is more optimal.